A délszláv népek nemzetiségi mozgalmai a 19. században - Heka László (Szegedi Tudományegyetem Állam- és Jogtudományi Karának tudományos bizottsága Szeged, 2010)
How to understand the history of nationalities of the historic Hungary, surfaced first time inl 848 as a central issue. Half of the old Hungary's population started movements for self-governance, just at the dawn of the freedom fighting of Hungary, posing a serious, and most important problem. The problem of self-reliance finghting of the minority nationalities posed great danger for the Hungarian nation, and poisoned the relationship of the Hungarian nation and its minorities. In Hungary the implementation of a single language system (as borrowed from Western societies) was burdened with difficulties, because the non-Hungarian minorities did not accept the process, they wanted to follow their own way. The introduction of the Hungarian language inflamed the minority circles, and speeded up their growing consciousness. They viewed the „Hungarization" as an intrusion into their education, and they were fearful, of their future existence, and the fading possibility of their future autonomy. The leaders of the revolution and freedom fighting, that the minorities wanted to preserve their collective rights, and they hoped to get that from the Vienna Habsburg Court. This boiling process has led to their opposition to the freedom-fighting, and their rising against Vienna, following the implementation of the absolutionist rule. The absolutionist rule terminated the self-governance system of the minorities, and it was only re-installed at 1868. The king signed the of Act XLIV of 1868, which explicitly spelled out the equalrights of the minorities, and their personal equal rights. The unanimous state doctrine was not well received by the minorities, and the majority viewed it as too big concession. Croatia was an exception. The „illir" movement aimed to establish a sovereign federal state incorporating the South-Slavic people. The Serbs also wanted a sovereign state under the rule of their king. At the end of the XIX. Century in Bosnia-Herzegovina, the population was divided by their religion (orthodox Serbs, catholic Croatians, and muslim bosnians) In the Austro-Hungarian Monarchy (1878-1918), their minority status was acknowledged, but only in 1970 they got their muslim identity acceptance, finally as Bosnia-Herzegovina.
Keywords: Bölcsészettudományok; Történettudomány és régészet